Analisis Kualitas Fisik dan Sosial Ekonomi Masyarakat sebagai Aspek Penilaian Keadilan Lingkungan Daerah Sekitar Tempat Pembuangan Akhir (TPA) Putri Cempo, Desa Jatirejo - Maria Theresia Sri Budiastuti; Hafizh Asfari; Prabang Setyono (Jurnal Wilayah dan Lingkungan, 2022)
Environmental justice is the same situation for all generations, both now and in the future. Environmental justice is measured based on differences in environmental impacts perceived by the community and statistics. This study aims to analyze environmental justice based on the physical and socio-economic of the community near the Putri Cempo Landfill, Jatirejo. This research was conducted in July-December 2021 in Jatirejo Village. The data collection on physical conditions was taken by laboratory tests, while socio-economic conditions were taken based on interviews and questionnaires. The results on the physical condition of the water showed that pH and iron did not exceed the standard, but the total coliform Too Numerous To Count (TNTC) and COD were quite high, 10.2 mg/L. The results of the air quality test showed that the values of NO2 and O3 were in accordance with the quality standards, 0.27 and 4.26 g/Nm3, respectively. Soil quality is in normal condition. From a socio-economic, the last education average of Jatirejo Village residents is senior high school, 36.66%. The majority of residents work as entrepreneurs, 35%. The average income of the community is IDR 500,000 – IDR 2,000,000, and some have very low incomes and even have no income. The suggested concept of environmental justice includes character building and improving human resources quality through the Job Training Center, Micro Small Medium Enterprises, Posyandu, 12-year free education, improving infrastructure, and waste management system. The conclusion of this study is that the environmental justice of the community around the Putri Cempo Landfill is quite good.